Mental health workers' experiences of support and help‐seeking following workplace violence: A qualitative study. (16th February 2021) - Rodrigues, Nicole C.; Ham, Elke; Kirsh, Bonnie; Seto, Michael C.; Hilton, N. Zoe
Abstract: The consequences of workplace trauma among mental health staff can include physical injuries and somatic disorders, professional exhaustion and burnout, depression, anxiety, and other occupational stress injuries. For the well‐being of staff and patients, there is a need to understand mental health workers' experiences following exposure to workplace trauma, any subsequent mental health problems, and the process of help‐seeking. The nuances of these experiences can best be captured through qualitative exploration. In this study, we explored inpatient mental health workers' experiences of support and help‐seeking following workplace violence. Four overall themes emerged from interviews with 12 participants: (i) validation as motivation for help‐seeking; (ii) stigma as a barrier to help‐seeking; (iii) gaps in services provided; and (iv) desire for accessible and effective trauma support and education. This study demonstrates the need for supportive management responses and peer support, access to specialized and confidential trauma‐informed mental health services, and reductions in stigma, victim blaming, and other barriers to help‐seeking among mental health workers.